Inovasi Produk Lumina Salad dalam Pengembangan Jiwa Kewirausahaan Mahasiswa di Surabaya - Ferdian, Farhan Ikbar; Putri, Khoirunisa Maylani; Ardani, Puteri Fadilla Fitri; Bierhoff, Rainhart (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the development of Lumina Salad as a creative product by students participating in the Student Creativity Program for Entrepreneurship (PKM-K) and its role in fostering student entrepreneurship in Surabaya. Lumina Salad was developed as a healthy food product tailored to the lifestyle needs of urban communities, particularly the younger generation, who prioritize practicality, health, and time efficiency. The research method used was a descriptive qualitative approach, with the Lumina Salad management team as the research subjects. Data collection techniques included in-depth interviews, direct observation of the production and marketing processes, and documentation of business activities. The phases of data reduction, data presentation, and conclusion drawing were used to examine the data. To verify the reliability of the study's conclusions, data validity was examined using triangulation of sources and methodologies. The results indicate that the development of Lumina Salad was driven by innovation in selecting fresh, high-quality local ingredients, implementing a practical presentation concept with modern, hygienic packaging, and establishing an affordable pricing strategy for consumers. Furthermore, the use of digital marketing through social media proved effective in increasing product visibility and expanding market reach. This business development process provides students with real-life entrepreneurial experience, encompassing business planning, operational management, decision-making, and business risk management. This study concludes that Lumina Salad not only produces healthy, economically valuable food products but also serves as an applicable entrepreneurial learning medium that fosters creativity, independence, and sustainability.